Human MuStem Cell Grafting into Infarcted Rat Heart Attenuates Adverse Tissue Remodeling and Preserves Cardiac Function - Rannou, Alice (Mol Ther Methods Clin Dev, 2020)
Myocardial infarction is one of the leading causes of mortality and morbidity worldwide. Whereas transplantation of several cell types into the infarcted heart has produced promising preclinical results, clinical studies using analogous human cells have shown limited structural and functional benefits. In dogs and humans, we have described a type of muscle-derived stem cells termed MuStem cells that efficiently promoted repair of injured skeletal muscle. Enhanced survival rate, long-term engraftment, and participation in muscle fiber formation were reported, leading to persistent tissue remodeling and clinical benefits. With the consideration of these features that are restricted or absent in cells tested so far for myocardial infarction, we wanted to investigate the capacity of human MuStem cells to repair infarcted hearts. Their local administration in immunodeficient rats 1 week after induced infarction resulted in reduced fibrosis and increased angiogenesis 3 weeks post-transplantation. Importantly, foci of human fibers were detected in the infarct site. Treated rats also showed attenuated left-ventricle dilation and preservation of contractile function. Interestingly, no spontaneous arrhythmias were observed. Our findings support the potential of MuStem cells, which have already been proposed as therapeutic candidates for dystrophic patients, to treat myocardial infarction and position them as an attractive tool for muscle-regenerative medicine.